Severe Recurrent Pancreatitis in a Child with ADHD after Starting Treatment with Methylphenidate (Ritalin) - Suheil Artul; Faozi Artoul; George Habib; William Nseir; Bishara Bisharat; Yousif Nijim (Case Reports in Gastrointestinal Medicine)
We present a case of a 10-year-old boy, who had severe relapsing pancreatitis, three times in two months within 3 weeks after starting treatment with methylphenidate (Ritalin) due to attention deficit hyperactivity disorder (ADHD). Pancreatitis due to the use of (methylphenidate) Ritalin was never published before. Attention must be made by the physicians regarding this possible complication, and this complication should be taken into consideration in every patient with abdominal pain who was newly treated with Ritalin.